Cardioprotective of Ethanol Extract of Black Turmeric (Curcuma Caesia Roxb) on Doxorubicin Induced Rats - Pratiwi, Nadya; Wahyudin, Elly; Cangara, Muhammad Husni (Sarana Ilmu Indonesia (salnesia), 2024)
Discovery of black turmeric's anti-radical, anti-inflammatory properties and ability to inhibit the growth of tumor cells. This study aimed to evaluate the cardioprotective effects and identity the effect of black turmeric (Curcuma caesia Roxb) ethanol extract in preventing cardiac damage in mice induced by doxorubicin. The experimental design employed is a pre-post test control group design. The study used male Wistar rats weighing between 150-200 grams, divided into 6 groups, with each group consisting of 4 rats. The first group, serving as the normal group, was only provided with food and water. The second group received Na-CMC as a negative control, while the third group was given Vitamin E as a positive control. The fourth, fifth, and sixth groups were administered suspensions of black turmeric extract at doses of 100, 300, and 500 mg/kg BW, respectively. The rats were induced with doxorubicin at a dose of 5 mg/kg BW once a week for 3weeks. On the final day of treatment, the rats were fasted for 18 hours, anesthetized, and blood samples were taken for analysis. The rats were also secured on a surgical board. Following induction, CKMB and LDH levels were measured again, and histopathological observations were conducted. The results showed CKMB levels indicated significant differences between groups with p<0,05 (0,025), while LDH levels did not show significant differences with p-value>0,05 (0,225). Histopathological examination of the heart revealed improvements in function and structure in the group IV.